Comparative Growth and Yield of Multipurpose Trees in Semi-arid Natural Grassland - Raj, P; Rao, G R; Solanki, K R; Ramana, D B V (Annals of Arid Zone, 2016)
Studies on comparative growth and production of 12 multipurpose tree species (MPTS) from 1988 to 1995 under Dichallthilllll alllllllatwn-dominated natural grassland revealed that 6 trees viz., Albizia alllara, A. lebbek, Acacia tortilis, Dichrostachys cillerea, Lellcaella lellcocephala and POllgalllia pillilata had better ~rowth (leaf fodder and fuel wood) and production, as well as higher crude protein In leaf fodder under this agro-c1imatic region. Thus, the above six MPTS are suitable for introduction in such type of grassland for getting the higher and nutritious leaf fodder as well as fuel wood.